Storia, redenzione a tempo messianico in Walter Benjamin - Tagliacozzo, Tamara (B@belonline, 2022)
Walter Benjamin’s concept of history is a construction where the messianic idea, the perfect world, is present in every ‘now of knowability’ in which the monadological ‘dialectical image’ presents itself as the actualization of moments of an unredeemed past that is redeemed in knowledge and afterwards in political action. The relation between past and present is given in the dialectical image, in the concept of history, in a messianic interruption of the course of history. This owes to the Jewish doctrine of the Kabbalah, to Kant (and Cohen) and to Marx. The ethical, political and «historical task» pertaining to the collective agent and subject of knowledge is founded on a conception of time that is not empty and mechanical, but that is full, intensive, and redemptive: it is the messianic time.